Effects Of Expectation, Perception, Disconfirmation, Satisfaction, Brand Trust, And Risk Perception On Premium Bottled Water Repurchase Intention Among Consumers In Nigeria - Oteino, Ojatta Dominic (2018)
Repurchase intention is associated with low operating costs, improved profitability, competitive advantage, and long-term business growth. Retaining positive repurchase intention among existing consumers requires businesses to invest in strategies that maximize consumers satisfaction. However, repurchase intention is too often negative or non-existent even where consumers are satisfied. Previous research report significant effects of expectation, disconfirmation, perception, satisfaction, brand trust, and risk perception on consumers repurchase intention. Nonetheless, there is lack of research on how the relationships amongst these factors impact consumers repurchase intention of premium bottled water (PBW). Grounded on the Expectation Disconfirmation Theory, this study investigates the effects of expectation, expectation disconfirmation, perception, satisfaction, brand trust, and risk perception on consumers repurchase intention of PBW brands in Nigeria.